2014
DOI: 10.1088/0004-6256/148/5/92
|View full text |Cite
|
Sign up to set email alerts
|

Young Stellar Object Variability (Ysovar): Long Timescale Variations in the Mid-Infrared

Abstract: The YSOVAR (Young Stellar Object VARiability) Spitzer Space Telescope observing program obtained the first extensive mid-infrared (3.6 and 4.5 µm) time-series photometry of the Orion Nebula Cluster plus smaller footprints in eleven other star-forming cores (AFGL 490, NGC 1333, (CCDs) revolutionized our ability to discern precisely optical variability trends and 2MASS did the same for near-infrared variability, the Spitzer Space Telescope (Werner et al. 2004) has allowed us to probe even small variations in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 132 publications
4
48
0
Order By: Relevance
“…The spacings between periodic shocks in jets and outflows support quiescent intervals anywhere from 10 4 yr down to 10 yr, separating bursts with an unknown range of accretion rates (Devine et al 1997;Raga et al 2002;Arce et al 2013). Highcadence photometric surveys show luminosity variations at the 5-50% level on timescales of hours to weeks (Billot et al 2012;Stauffer et al 2014), though only some of that may be related to accretion variability (Morales-Calderón et al 2011;Rebull et al 2014). Despite the incomplete statistics, it appears that stronger accretion bursts occur less frequently than weaker ones.…”
Section: And For Fuormentioning
confidence: 97%
“…The spacings between periodic shocks in jets and outflows support quiescent intervals anywhere from 10 4 yr down to 10 yr, separating bursts with an unknown range of accretion rates (Devine et al 1997;Raga et al 2002;Arce et al 2013). Highcadence photometric surveys show luminosity variations at the 5-50% level on timescales of hours to weeks (Billot et al 2012;Stauffer et al 2014), though only some of that may be related to accretion variability (Morales-Calderón et al 2011;Rebull et al 2014). Despite the incomplete statistics, it appears that stronger accretion bursts occur less frequently than weaker ones.…”
Section: And For Fuormentioning
confidence: 97%
“…Recent surveys have found that the vast majority of YSOs are variable in the mid-infrared on timescales of days to weeks Rebull et al 2014), expanding on earlier ground-based near-infrared studies (e.g., Carpenter et al 2001). These surveys have also revealed additional clues as to the structure of the inner disk.…”
Section: Introductionmentioning
confidence: 92%
“…The For evenly sampled data other techniques like the autocorrelation of the light curves may be used to identify variable sources (e.g., Rebull et al 2014). However, our light curves are sampled fairly inhomogeneously and any kind of interpolation of gaps will introduce additional uncertainties; therefore we did not apply the autocorrelation technique here.…”
Section: Identification Of Variable Stars In Separate Filtersmentioning
confidence: 99%